Comparative analyses of antimicrobial activities of Bauhinia purpurea L., Dicranopteris linearis (Burm.f.) Underw., Melastoma malabathricum L. and Muntingia calabura L. methanolic extracts - Chuah, Ee Ley (2014)
Microbial infections are common issues that happen in the society. However, the emergence of multidrug-resistant microbials have caused complications in diagnosing the effective treatments for patients to overcome the infections. The efficacy of antimicrobial agents available in the market against such resistant isolates have been compromised, aside from the side effects to human health caused by prolonged use of these drugs. The vast usage of traditional medicines in folklore era has triggered interest to seek for alternatives from plant sources in battling against these increasing multidrug- resistant microbials. This research aimed to compare a few assays in determining the antimicrobial activities of plant extracts. This study utilised disc diffusion assay, broth microdilution assay (visual turbidity inspection and spectrophotometric analysis) and colorimetric resazurin microtiter assay (REMA) to analyse the antimicrobial activities of methanolic leaf extracts of Bauhinia purpurea (BPME), Dicranopteris linearis (DLME), Melastoma malabathricum (MMME) and Muntingia calabura (MCME) against four American Type Culture Collection (ATCC®) bacterial strains, which were Escherichia coli ATCC® 25922™, Pseudomonas aeruginosa ATCC® 27853™, Staphylococcus aureus ATCC® 25923™ and Staphylococcus aureus ATCC® 700699™. Comparative analyses showed that MMME and MCME elicited greater antimicrobial activities compared to BPME and DLME, with Gram-positive strains showing greater susceptibility patterns. Interestingly, the methicillin-resistant Staphylococcus aureus/vancomycin-intermediate S. aureus (MRSA/VISA) strain employed in this study showed the greatest susceptibility pattern among the tested bacterial strains. Comparative analyses revealed that REMA would be a more accurate method to determine the minimum inhibitory concentration (MIC) values as the absence of colour change of resazurin may not signify the non-viability of bacterial cells, but rather the bacteriostatic phase of cells due to inhibitory effect of antimicrobial agents (plant extracts). On the other hand, conventional plating method on solid growth media and observation of bacterial growth after overnight incubation would be a more precise way to determine the minimum bactericidal concentration (MBC) values due to the bacterial growth can be observed easily by observing any presence of single colonies on the surface of solid media. Growth indicator which is usually employed in determining the MBC values may not be the most accurate way to determine the MBC values. This is so as it was observed that the bacterial suspension treated with methanolic leaf extract which changed the colour of resazurin from blue to purple did not harbour any bacterial growth upon plated on solid growth media. This may be due to the toxicity of antimicrobial agents which might have impaired the cell's viability and its ability to proliferate. This probably resulted the reduced capability of the cell to reduce resazurin (blue pigments) to resorufin (pink pigments). Disc diffusion assay can be employed as a preliminary screening for antimicrobial activities of potential antimicrobial agents before further tests are carried out, whereas spectrophotometric analysis can be employed as a supplementive measurement to observe the susceptibility pattern of microbials when treated with antimicrobial agents.